2015
DOI: 10.1111/1755-0998.12457
|View full text |Cite
|
Sign up to set email alerts
|

Development of chloroplast genomic resources for Cynara

Abstract: In this study, new chloroplast (cp) resources were developed for the genus Cynara, using whole cp genomes from 20 genotypes, by means of high-throughput sequencing technologies. Our target species included seven globe artichokes, two cultivated cardoons, eight wild artichokes, and three other wild Cynara species (C. baetica, C. cornigera and C. syriaca). One complete cp genome was isolated using short reads from a whole-genome sequencing project, while the others were obtained by means of long-range PCR, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In the study of the Vicia species, no allelic polymorphism were detected in matK region (Raveendar et al 2015), suggesting the high level of conservation of standard barcode locus among the Vicia species. In the chloroplast genome analysis of 20 genotypes belonging to genus Cynara, a total of 73 InDels were identified with 39 polymorphic simple sequence repeats (SSRs) and 34 other InDels (Curci et al 2016), exhibiting the level of quantity of InDels within genus. In this analysis, we compared Allium victorialis chloroplast genome with those of Veratrum patulum and identified five potential regions for future DNA markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of the Vicia species, no allelic polymorphism were detected in matK region (Raveendar et al 2015), suggesting the high level of conservation of standard barcode locus among the Vicia species. In the chloroplast genome analysis of 20 genotypes belonging to genus Cynara, a total of 73 InDels were identified with 39 polymorphic simple sequence repeats (SSRs) and 34 other InDels (Curci et al 2016), exhibiting the level of quantity of InDels within genus. In this analysis, we compared Allium victorialis chloroplast genome with those of Veratrum patulum and identified five potential regions for future DNA markers.…”
Section: Discussionmentioning
confidence: 99%
“…These five regions carry multiple InDels ranged from 1-63 bp in size. InDels in chloroplast genome serve as a useful marker system and outperforms SNPs because PCR products are easily discriminated by size (Melodelima et al 2013;Chaney et al 2016;Curci et al 2016;Daniell et al 2016). Intergenic regions are useful sources for InDels, because these regions underwent relatively rapid mutation due to the less evolutionary constraint.…”
Section: Discussionmentioning
confidence: 99%
“…For the artichoke samples, the four main morpho-agronomic groups were considered: the small headed early types (˝Catanesi˝), the spiny early types (˝Spinosi˝), the violet late types (˝Violetti˝), and the large headed late types (˝Romaneschi˝) [ 23 ]. Several other accessions, belonging to none of the above typologies, were analysed [ 12 , 31 ]. The cultivated cardoon germplasm included material originating from the main regions where this vegetable is grown, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have shown that chloroplast genome mutations are not random but cluster at “hotspots” [ 16 , 19 , 20 , 21 ], and this mutational dynamic has resulted in highly variable regions in the genome. Chloroplast genome single nucleotide polymorphism (SNP), SSR, and indel markers have been developed in recent studies, as they show high abundance in the genome and improve population resolution [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%